Transformational Leadership and Organizational Climate as Predictors of Positive Discipline Culture in Indonesian Elementary Schools - Rani Setyawati; Supandi Supandi; Nurkolis Nurkolis (Journal of Innovation and Research in Primary Education, 2026)
Positive discipline has become a key priority in elementary education as schools shift from punitive practices toward restorative approaches. However, implementation varies widely across schools and is likely shaped by leadership and organizational conditions. This quantitative ex post facto study examined the extent to which principals' transformational leadership and school organizational climate predict positive discipline culture in Indonesian public elementary schools. Participants were 130 teachers from 20 public elementary schools in Tanggungharjo District, Grobogan Regency, selected using proportionate stratified random sampling. Data were collected through validated Likert-scale questionnaires measuring transformational leadership, organizational climate, and positive discipline culture. Pearson correlation and hierarchical regression analyses were conducted. Results showed that transformational leadership was strongly associated with positive discipline culture (r = 0.761, p < .01) and explained 57.9% of its variance. Organizational climate was also positively associated with positive discipline culture (r = 0.674, p < .01) and explained 45.5% of its variance. In the multiple regression model, both variables jointly explained 70.0% of the variance in positive discipline culture, with leadership showing a larger standardized contribution (β = 0.567) than climate (β = 0.398). These findings indicate that strengthening transformational leadership practices and improving school climate may be strategic levers for embedding positive discipline as sustainable school culture.